Understanding Development from the Perspective of University Students in Bangladesh - Mahmudur Rahman (Journal of Management and Administration Provision, 2023)
The meaning of the term "development" is common parlance. Although its limited meaning is one of improvement, its broader significance is far-reaching. But the exact significance might be different for each individual. Some people may anticipate a certain breakthrough while others may not. College kids have a huge impact on society. And the ideas they have deserve recognition. College students in Bangladesh have divergent views on what constitutes progress in the country. While many students believed that progress could be ensured only through personal growth, others held that development required changes to their physical environment. Many people believe they are living a fully developed life, but in reality, they are not. Alternatively, dimensions may have a range of connotations. The question is whether these factors are seen as crucial by the graduates. How well-versed they are in the concept of growth. There are also developmental roadblocks to consider. The main goal of this research is to find out the thoughts of university students of Bangladesh and get to know what is the meaning if development to them. For more in-depth analysis there are some objectives to get information about development and to get the opinions and analyze them.